(untitled) (Fiep Bulletin - online, 2014)
Asymmetries in muscle strength exceeding 15% between the two lower-limbs are considered potential causative factors ofinjury. The objective of the study was to determine the percentages of strength asymmetry between the lower-limbs of school children andinvestigate whether values >15% correlated with performance in speed drills. The sample was composed of N=138 students (72 M and66 F, 12.0±1.1 yrs; 52.4±11.1 Kg, 159±0.08 cm) attending the first 3 years of an Italian middle school. Lower-limb strength asymmetrieswere assessed using the tests: One-Leg Hop (OLH ), One-Leg Triple Hop (OLTH ) and Side Hop (SH ); running speed was assessed usingthe tests: 10 and 20m sprint, 10x5m Shuttle Sprint and 4.115m Side Steps and Forward (4.115m SSF ). To test for correlations betweenlower-limb asymmetries and running speed performance, Pearson’s correlations were calculated. Statistical significance was consideredfor p<0.05. Performances in the OLTH test revealed that an astonishing 65% of male school children present levels of asymmetry >15%.Pearson’s correlations revealed that values of asymmetry >15% in the OLH and OLTH tests positively correlate with performance inthe shuttle test (r=0.452, N=23; p<0.05) and 4.115m SSF test (performed on the right leg; r=0.706, N=25; p<0.01). Thus, running drillsrequiring lateral movements and changes in direction are affected by imbalances in lower-limb muscle strength in children and adolescents. Compensation strategies aimed at diminishing the percentage of strength asymmetry should be introduced into physical education lessons within schools in order to reduce the risk for injury.